The Implementation of Wayground for Speaking Activities and Students’ Responses in an Inclusive Junior High School EFL Classroom - Wahyuni, Dela; Amin Dalimunthe, Ahmad (Universitas Jambi, Magister Program of English Education Department, 2026)
This study aimed to investigate the implementation of Wayground (formerly known as Quizizz) as a game-based learning platform to support speaking activities in an inclusive EFL classroom and to explore students’ responses toward its use. This study employed a descriptive qualitative research design. Data were collected through classroom observations, semi-structured interviews with the teacher and students, and documentation. The data were analyzed using thematic analysis based on Braun and Clarke’s (2006) framework. The findings revealed that Wayground was implemented through teacher-guided speaking activities in which questions were displayed via a projector and students were encouraged to respond orally in English. The findings also indicated that students demonstrated active participation in speaking activities and classroom interactions during the implementation of Wayground. In addition, students perceived the learning activities as engaging and enjoyable, which encouraged participation among learners with different levels of speaking ability and self-confidence. Nevertheless, several challenges were identified, including students’ limited vocabulary, technical issues, and time constraints during the implementation process. Overall, the findings suggest that Wayground can be implemented as a game-based learning platform to support speaking activities in an inclusive EFL classroom. The study also highlights its flexible use across different classroom contexts and describes students’ responses toward its implementation in English language learning. Furthermore, the findings provide insights into how Wayground was implemented in speaking activities and how students responded to its use in an inclusive EFL classroom.